(untitled) (American Journal of Islam and Society, 2010)
This conference, organized by the Faculty of Usuluddin at Sultan Sharif Ali Islamic University (UNISSA), was held on 24-25 February 2010 at the Rizqun International Hotel in Gadong, Brunei. The 119 local and 40 international participants presented 78 working papers. Local and international media outlets and representatives of government bodies, as well as officers from the Department of Community Development, the Ministry of Religious Affairs’ Syariah Affairs Department, and the Brunei Economic Development Board, also attended. One of the main objectives was to clear up misconceptions about Islam in order to bridge the gap and strengthen relationships and cooperation between Muslim and western countries. Abdul Muthalif Afuwardeen (conference co-chairman; dean, Faculty of Usuluddin, UNISSA) welcomed the audience and spoke of the importance of religion and peace and how Islam and Muslims have been wrongly portrayed as symbols of terrorism, underdevelopment, and mockery. Ustaz Hj Abdul Aziz Juned (state mufti) opened the event on behalf of Sultan Has-sanal Bolkiah and urged participants to spread the truth about Islam worldwide. Keynote speaker Ismail Ibrahim (chariman of Islam Hadhari, National University of Malaysia), analyzed how many westerners consider Islam a religion of violence, war, and suppression due to their misunderstanding of jihad. He also called for mutual understanding among all parties ...